2006
DOI: 10.1038/sj.bdj.4813952
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning of the edentulous maxilla

Abstract: The predictability of successful osseointegrated implant rehabilitation of the edentulous jaw as described by Branemark et al., 1 introduced a new era of management for the edentulous predicament. Implant rehabilitation of the edentulous maxilla remains one of the most complex restorative challenges because of the number of variables that affect both the aesthetic and functional aspect of the prosthesis. 2 Among the prosthesis designs used to treat the edentulous maxilla are fixed or removable implant-supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 10 publications
(13 reference statements)
0
59
0
Order By: Relevance
“…[9] The phenomenon of residual ridge resorption (RRR) following removal of teeth has been well observed and documented in literature. [10,11] While the bone loss following the removal of teeth is stated to be rapid, progressive, irreversible and inevitable, it is equally well observed that bone is maintained around standing teeth and implants.…”
Section: Surgical Intervention (Vestibuloplasty and Excision Of Flabbmentioning
confidence: 99%
“…[9] The phenomenon of residual ridge resorption (RRR) following removal of teeth has been well observed and documented in literature. [10,11] While the bone loss following the removal of teeth is stated to be rapid, progressive, irreversible and inevitable, it is equally well observed that bone is maintained around standing teeth and implants.…”
Section: Surgical Intervention (Vestibuloplasty and Excision Of Flabbmentioning
confidence: 99%
“…Since, as the number of input factors increases, the number of cases required for teaching the ANN also increases, the collected data were presented to two expert prosthodontists, both of whom were faculty members with more than 10 years of experience in implant dentistry. They were asked to address the specific factors that affect their decision on the final prosthetic design for each patient with consideration of the standards presented by Misch (2005), Zitzman (2000), and Jivraj et al (2006). The number of factors was then limited to the most relevant ten; and factors such as implant length and demographic data were omitted.…”
Section: Methodsmentioning
confidence: 99%
“…Records with incomplete data regarding patient examination or surgical procedure (2000), and Jivraj et al (2006) discussed an average of 15 factors that should be considered regarding the treatment planning of an edentulous maxilla with dental implants. The priorities of each factor (weighting) in the treatment-planning sequences were not initially determined accurately.…”
Section: Methodsmentioning
confidence: 99%
“…34, 161 However, both surgical and prosthodontic acumen is required, since the implants must be congruent with the crowns, and the creation of a natural morphology of the tooth/tissue junction is rigorous. Complete fixed, segmented rehabilitations supported by 6 to 8 rough surface implants have been documented in a review with a 96.4% prosthodontic survival rate at the 10-year endpoint.…”
Section: The Metal Ceramic Designmentioning
confidence: 99%